Rhetorical analysis of the compositions of the original vallenato or minstrel musical genre - Seni, Giuliano Dante (2024)
Vallenato is a musical genre from the Colombian Caribbean, related to the history of this region located on the shores of the Caribbean Sea, originally performed by minstrels, usually traveling peasants who rode on mules along the Magdalena Grande region with an accordion in their hands. The savanna landscapes and town festivals were a source of inspiration to compose songs that over time became classics. The purpose of this research is to analyze the rhetorical components within the narratives of the original vallenato genre, particularly the presence of elements such as inventio, dispositio and elocutio. For this purpose, the corpus was created from the selection of some of the main minstrels of this musical genre and, in addition, compositions by these performers. It was found that the original vallenato genre is mainly made up of true stories, for the most part, told in the form of anecdotes by its protagonists. They raise conflicts between two forces and use their greatest expressive force to expose the situation and the details of the events, but mainly, to reiterate the feelings and emotions of the narrator minstrel which, incidentally, do not always revolve around the love of a woman, but also to professional rivalry, all with the background landscape of the Colombian Caribbean and the circumstances of its historical context.